(untitled) (Experimental biology, 2015)
The research revealed that an adequate temperature impact test on heat-sensitive zone result in a relatively rapid recovery all the investigated of indicators after treadmill test. As a result of thermal stimulation of the skin zones are improving the functional condition of the organism, raises performance capacity both healthy people and patients with abnormalities of the cardiovascular system.